SANKSI HUKUM BAGI PELAKU LAYANAN PENDANAAN DARING ILEGAL - Nurhayati, Nurhayati; Widodo, Ernu; Astutik, Sri; Subekti, Subekti (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study aims to examine the elements of criminal acts committed by perpetrators of illegal online financing services in Indonesia. With the rapid development of financial technology (fintech), online funding services have become an alternative for the public to access financing. However, the proliferation of illegal online funding services operating without permission from the Financial Services Authority (OJK) has given rise to various legal and social problems, such as misuse of personal data, extortion, and unethical collection practices. This study uses a normative juridical method with a legislative, conceptual, and case approach to analyze the legal sanctions that can be imposed based on the Electronic Information and Transaction Law (EIT Law) and the Criminal Code (KUHP).